2019
DOI: 10.3390/mps2020044
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Mass Spectrometry Imaging Linked with Top-Down Proteomics as a Tool to Study the Non-Small-Cell Lung Cancer Tumor Microenvironment

Abstract: Advanced non-small-cell lung cancer (NSCLC) is generally linked with a poor prognosis and is one of the leading causes of cancer-related deaths worldwide. Since only a minority of the patients respond well to chemotherapy and/or targeted therapies, immunotherapy might be a valid alternative in the lung cancer treatment field, as immunotherapy attempts to strengthen the body’s own immune response to recognize and eliminate malignant tumor cells. However, positive response patterns to immunotherapy remain unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
(66 reference statements)
0
24
0
Order By: Relevance
“…Identification of these three peptides of interest was not possible with top-down peptidomics, as performed earlier for an identification of other MALDI MSI targets with higher-energy collisional dissociation (HCD) [23]. Although the precursors for these peptides could be selected for fragmentation, the corresponding fragmentation spectra did not yield sufficient fragments to allow peptide identification.…”
Section: Peptides Of Interest Are Identified As Neutrophil Defensin 1mentioning
confidence: 99%
See 3 more Smart Citations
“…Identification of these three peptides of interest was not possible with top-down peptidomics, as performed earlier for an identification of other MALDI MSI targets with higher-energy collisional dissociation (HCD) [23]. Although the precursors for these peptides could be selected for fragmentation, the corresponding fragmentation spectra did not yield sufficient fragments to allow peptide identification.…”
Section: Peptides Of Interest Are Identified As Neutrophil Defensin 1mentioning
confidence: 99%
“…We have demonstrated earlier that MALDI mass spectrometry imaging (MSI) is a powerful tool to visualize the NSCLC tumor microenvironment based on the endogenous peptidomic profile (m/z range 800-5000 Da) [23]. The analysis of differential peptide expression in the tumor versus nontumor region revealed two molecules at m/z 3369.5 and m/z 3440.6.…”
Section: Maldi Mass Spectrometry Imaging For Predictive Biomarker Dismentioning
confidence: 99%
See 2 more Smart Citations
“…For each m / z , an image is constructed that reflects the spatial distribution of the sample chemical composition. This technique has been used to study tumor microenvironments [ 136–143 ] and other tissue sections in an attempt to segregate diseased versus nondiseased tissue, providing potential protein or biomarker targets for treatment. While high resolution mass spectrometry in clinical research has shown promising results, the time and cost involved in acquiring and analyzing data has been a significant barrier of entry for use in routine clinical care.…”
Section: Mass Spectrometrymentioning
confidence: 99%